Notes on the genus Zeravschania (Apiaceae) with description of two new species from Afghanistan and Iran - Kljuykov, Eugene; Terentieva, Elena; Ukrainskaja, Uliana; Lyskov, Dmitry (Phytotaxa, 2019)
Two species of Apiaceae are described as new to science: Zeravschania khorasanica from the Khorasan Province, eastern Iran, and Z. podlechii from the Ghor Province, central Afghanistan. Zeravschania khorasanica is related to Z. regeliana and Z. scabrifolia, but differs in rigid remains of petioles and sheaths, deeply laciniate ultimate segments of leaves, and broad-keeled ribs of mericarps. Zeravschania podlechii differs from other species of the genus in multiple stems, short internodes, dichotomous branching, and an unusual life form (сushion plant). In addition, Z. knappii is transferred to the genus Dichoropetalum on the basis of morphological evidence.